2010
DOI: 10.1073/pnas.1002258107
|View full text |Cite
|
Sign up to set email alerts
|

Economic choices can be made using only stimulus values

Abstract: Decision-making often involves choices between different stimuli, each of which is associated with a different physical action. A growing consensus suggests that the brain makes such decisions by assigning a value to each available option and then comparing them to make a choice. An open question in decision neuroscience is whether the brain computes these choices by comparing the values of stimuli directly in goods space or instead by first assigning values to the associated actions and then making a choice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 35 publications
8
90
2
2
Order By: Relevance
“…S8), as was the case in a recent recording study that focused on the lOFC (34). In contrast, our hypothesis that the mOFC is concerned with value-guided decision-making can account for previous findings; it predicts mOFC signals should correlate with the values of the choice options being considered and then with the value of the choice finally taken (3,4,23). Moreover, an account of the lOFC that focuses on value assignment predicts lOFC activation to errors if the errors occasion reassignment of values to options.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…S8), as was the case in a recent recording study that focused on the lOFC (34). In contrast, our hypothesis that the mOFC is concerned with value-guided decision-making can account for previous findings; it predicts mOFC signals should correlate with the values of the choice options being considered and then with the value of the choice finally taken (3,4,23). Moreover, an account of the lOFC that focuses on value assignment predicts lOFC activation to errors if the errors occasion reassignment of values to options.…”
Section: Discussionmentioning
confidence: 49%
“…The precise nature of the mOFC's involvement, however, remains to be specified. Functional MRI studies have reported that ventromedial frontal activity, but not lOFC activity, reflects the value of the option that will be chosen but also the value of options that will go unchosen (3,4,23). In some cases, but not all (23), a value-difference signal suggests a value comparison process within the ventromedial frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that decisions can be taken in either stimulus-based or action-based decision space, depending on the context, and that these decisions engage different neural substrates. These findings argue for material-specific contributions of dACC to action selection, and OFC to stimulus selection, based on value (Rushworth et al, 2007a;Buckley et al, 2009;Hayden and Platt, 2010;Wunderlich et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…Further, it is not clear whether decisions proceed stepwise, with choice resting on the transformation of stimulus value to action. Indeed, fMRI evidence argues that action value representations in dACC are not needed for stimulus-based decision making (Wunderlich et al, 2010). An alternative view is that value influences choices between stimuli and between actions through distinct, perhaps parallel, mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different kinds of decisions involve different prefrontal areas. Value-based decision making involves ventromedial PFC (Basten et al, 2010;Philiastides et al, 2010;Wunderlich et al, 2010). Predictive coding of categories also involves mPFC (Summerfield et al, 2006).…”
Section: Prefrontal Cortexmentioning
confidence: 99%